Covalently constrained alpha-helices - Arora, Paramjit (Henry Stewart Talks, 2008)
Alpha-helices, Role of alpha-helices in protein structure, Alpha-helices in protein-protein and protein-nucleic acids interactions, Stabilization of short peptides in alpha-helical conformation, Side-chain cross-linked helices, Hydrogen-bond surrogate based alpha-helices
Archived at 2021/02/25